Artistic Image in Fashion Design: Methods for Creating Avant-Garde Clothing - Toshmuhammedova Iroda Alibek qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article explores the creation of artistic images in fashion design, focusing on avant-garde clothing. Avant-garde design encourages experimentation, innovation, and the integration of unconventional artistic elements into garments. The study examines methods for combining color, texture, and form, as well as incorporating cultural and contemporary artistic influences to develop unique and expressive clothing designs.